PREVALENCE AND ASSOCIATED FACTORS OF SKIN DISEASES IN LONG HIEP COMMUNE, VINH LONG PROVINCE, 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to investigate the disease patterns and associated factors among patients with dermatological conditions.Methods: A cross-sectional descriptive study was conducted on 118 patients with skin diseases in Long Hiep commune, Vinh Long province, in 2025.Results: The four most common skin conditions were atopic dermatitis (29.7%), acne vulgaris (23.7%), contact dermatitis (12.7%), and urticaria (11.0%). The findings indicated that occupation and ethnicity were the main demographic factors associated with the prevalence of common skin diseases. In addition, a history of allergy was associated with acne. Regarding behavioral factors, activities such as sun exposure of more than 30 minutes per day, use of sun-protective measures (e.g., hats, masks), and the use of body wash or bar soap were significantly associated with the three major skin conditions: atopic dermatitis, acne, and urticaria.Conclusions: The study demonstrated that the prevalence of skin diseases in the community is diverse. The findings highlight the role of environmental and behavioral factors in the development of skin diseases, suggesting the need to strengthen health education, communication, and appropriate preventive interventions at the community level.
Keywords: Dermatological disease patterns, epidemiology, atopic dermatitis, Vinh Long.